Work Related Quality of Life (WRQoL) Survey of Surgical Residents at Tertiary Care Hospital - Ullah, Tahmeed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To explore work-related quality of life of surgery residents in a Tertiary Care Hospital in Khyber Pakhtunkhwa.Study Design: Explanatory Sequential Mixed Method studyPlace and Duration of Study: Surgical and Allied Departments, Hayatabad Medical Complex Peshawar, Pakistan from Mar to May 2020.Methodology: Postgraduate residents from surgical and allied specialties were given standard Work-Related Quality of Life (WRQoL) questionnaire. WRQoL scores were calculated for the residents. In the second stage, postgraduate residents with low scores were interviewed until the saturation of data was reached. For quantitative data collection we used convenient non-probability sampling technique and for qualitative data we used the extreme case purposeful sampling technique.Results: A total of thirty-nine residents submitted a filled WRQoL questionnaire. The mean WRQoL score in our study was 74.82±15.84. A total of 17(43.6 %) residents had low WRQoL scores. Components of WRQoL scores were also studied for each resident. Stress at work (SAW) showed a significant increase in female residents compared to male residents (p=0.003). Conclusion:  More than 43% of the residents in surgery reported low quality of life at workplace. The score is predominantly low in female and junior residents. The major contributor is the stress at work. Significant effort needs to be made to improve the working conditions of surgical residents. This study also opens the way for further work into the burnout of physicians and nurses.